1994
DOI: 10.2748/tmj/1178225757
|View full text |Cite
|
Sign up to set email alerts
|

Pointwise convergence of Hermite-Fejér interpolation of higher order for Freud weights

Abstract: This paper is concerned with the approximation by Hermite-Fejer interpolation of higher order based at the zeros of orthogonal polynomials with respect to the typical Freud weight. We will prove a convergence result for even order and a divergence result for odd order. Introduction.The purpose of this paper is to investigate the pointwise convergence of Hermite-Fejer interpolation of higher order based at the zeros of orthogonal polynomials with respect to a Freud weight of the form exp( -x m ) with an even po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…For the future works such as the differential relation of orthogonal polynomials with respect to the exponential weights, we need further assumptions with respect to Q(x) (see [1,3]). In the following, we introduce a new weight subclass of the weight class in Definition 1.1.…”
Section: Remark 12 (A)mentioning
confidence: 99%
“…For the future works such as the differential relation of orthogonal polynomials with respect to the exponential weights, we need further assumptions with respect to Q(x) (see [1,3]). In the following, we introduce a new weight subclass of the weight class in Definition 1.1.…”
Section: Remark 12 (A)mentioning
confidence: 99%
“…In Section 2, we will introduce the classes F (C 2 ) and F (C 2 +) , and then, we will obtain some relations of the factors derived from the classes F (C 2 ) , F (C 2 +) and the classes L(C 2 +) , L(C 2 +) . Finally, we will prove the main theorems using known results in [1][2][3][4][5], in Section 3. We say that f : ℝ ℝ + is quasi-increasing if there exists C > 0 such that f(x) ≤ Cf(y)…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…We see that L n ( f ; x)=L n (1, f; x) is the Lagrange interpolation polynomial and L n (2, f ; x) is the ordinary Hermite Feje r interpolation polynomial. In [3] we showed the following. Recently, for the Lagrange interpolation polynomial L n ( f ; x), Lubinsky and Matjila [6] obtained the following nice result.…”
Section: ) L (R)mentioning
confidence: 99%
“…1Â2 1(mÂ2)Â1(m+1Â2)] 1Âm be Freud's constant, and let :=m(mÂ2) (m&1)Âm ( m&2 mÂ2&1 ) ; m&1 . In [3], we showed that the proposition held for x kn # [%, 3], where % and 3 are positive constants. We omit the proof of Proposition 5.3, because we can show it by careful repeating the same line of the consideration as one in [3].…”
Section: Proof Of Theoremmentioning
confidence: 99%
See 1 more Smart Citation